Legitimität, Sicherheit, Autonomie Eine philosophische Analyse der EU-Sicherheitspolitik im Kontext der Digitalisierung - Orrù, Elisa (Sicherheit und Gesellschaft. Freiburger Studien des Centre for Security and Society, 2021)
This book examines the current dynamic and momentous development of European security policy. In doing so, it provides an important and original contribution to both practical philosophy and to the fields of security studies and European studies. Using concrete analyses and by offering possible solutions to certain problems, the book develops an approach that is embedded in reality and which, at the same time, insists on theory and normativity. It focuses on the characteristics of new security technologies and ways in which security is understood as well as their influence on the 'Copernican Revolution' of the modern age, through which individuals and the protection of their fundamental rights have become the focus of political legitimation.